Situational analysis for the curriculum development of the University of the Philippines College of Architecture Master of Architecture program - Ozaeta, Emilio Ursua (College of Architecture, University of the Philippines Diliman, 2008)
Curriculum development involves not only the writing of the actual curriculum itself but also the preparation of a foundation on which to base the decisions made in its writing. In this study the context of the realities of the profession of architecture and the building construction and real estate industry are examined as a basis for the curriculum development of graduate program for architecture. Using Print's theoretical model, specific issues within the current program are determined, factors arising from those issues are identified and specific data aligned with those factor are gathered. The result is a set of recommendations grounded in the reality of the situational context that may be used as the foundation upon which the College of Architecture may developed the new curriculum program.